Bible as the Cultural but Colonial Text: A Naga Perspective - Ragui, T. (University of jaffna, 2024)
When colonials, such as American Baptist missionaries and British administrators and or ethnographers, introduced Christianity to the Nagas in the late-nineteenth and early twentieth centuries, they brought with them a supernatural view of the Bible. Along with a set of colonial beliefs founded on written texts, this viewpoint was imposed on the Naga communities. However, Naga communities are a communitarian society who practise oral tradition and follow traditional-primal religion. The enforcement and adoption of a textbased belief system in oral-based tribal-indigenous communities resulted in significant changes to their socioreligious systems. As colonial ideologies are implemented, the Bible gradually becomes the cultural text of the Nagas, dictating the means of expressing and preserving their identity, beliefs, and knowledge in public spaces, while the traditional heritage of the Nagas is prohibited and neglected or disregarded gradually. Using the Bible as the cultural text through such a rigid colonial lens, however, is not only an ineffective approach to addressing public concerns, but it also has disastrous consequences. For instance, Naga communities would speak, teach, and/or write about the Bible as though they were from the Global North, neglecting who they are as tribal-indigenous communities. Such a reading of the Bible would entail pursuing ready-made answers to everyday life situations, proof-texting it in different life’s circumstances, and failing to adequately consider the cultural-public context of the Nagas. Considering this reality, I argue for the need to decolonise the Bible, with a focus on its interpretation and application among the Nagas in Northeast India. This paper’s subject will be limited to the Tangkhul Nagas in particular and Naga communities in general.
Keywords: Decolonise the bible; Contextualize; Undertake Tribal Naga Reading